The General Government and the policy of the French governors in Algeria 1830-1900 - Mokhtari, Tayeb (The Algerian Historical Journal, 2026)
I discuss in this article the beginnings of colonial presence, where efforts were made to establish a colonial administration that served as a tool for the colonial project. At the forefront is the General Government in Algeria, headed by the Governor-General. in the year 1834, led by the Generals. I also discuss the African Commission's report, which emphasized the establishment of the position of Governor-General in its final report, embodied in the Decree of Annexation and the Organization of Algeria on July 22, 1834. I also address some changes introduced to this position, represented by the Law of Annexation in 1881 and the Decree of 1896. Furthermore, I discuss examples of policies implemented by the leaders and Governor-Generals during the period from 1830 to 1900.